PRESENTASI DIRIWANITA SEBAGAI SATUAN PENGAMANDIPUSAT PERBELANJAAN MAL SKA PEKANBARU - Wahyuda, Tegar; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The phenomenon of women run masculine professions can currently be found, one of them being a security unit. As a security guard are also required to run their nature as a wife and a housewife. This study aims to determine the front stage and back stage woman security at Mal SKA Pekanbaru.This study uses qualitative research with phenomenological approach. Subject of the study consisted of three security guards at the Mall SKA Pekanbaru women who have been chosen by purposive technique. The study used data collection techniques of observation, interviews, and research documentation. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.The results showed, first activity of the front stage (front stage) Mal SKA female guards are guarding the entrance activity Mall SKA, controlling basement, mobile floor, checking the criminal and maintaining office entrance. Manner that want to be perceived is the figure of the security firm, sprightly but still put forward the friendly attitude with a smile often to visitors with appearance of their attributes, hijab, cufflinks, uniform PDH (uniforms daily) complete with shoes PDH, PDL uniforms (uniforms outside) as well as makeup. Another attribute that female security guard coupling, rope chair complete with whistle, emblem, holograms in uniform, smile pin solution, haloan tango, mirrors, and metal detector. Second, the back stage female guards Mal SKA is activity to be a housewife and activities in the home environment. Manner which is perceived motherly attitude. But some attitude during the work sometimes helped too carried away though at the time I was at home such as assertiveness, discipline and lots of talk. This activity is also supported by the appearance of their attributes that negligee garments, clothing pregnant women, the hijab (when out of the house) as well as shirts and pants outfit.Keywords : Self Presentation, female guards, back stage, front stage